Zeroing in on leadership effectiveness: The methodological challenges of benchmarking leadership practices - Ames, Michael D. (International journal of value-based management, 1995)
Business success in the 21st century will be based on the widespread mastery of leadership roles, rather than on the directives of a professional or leadership elite. The first step for systematically enacting a leadership development agenda for our nation is to identify the factors, values or qualities most important to leadership effectiveness. Next, we must improve our understanding of how these guiding ideas and insights translate into what successful leaders do. As we perfect this understanding, we will need to operationally define the “best practices” of successful leaders. These best practices must then become “benchmarks’ for intensive leadership development efforts., This article considers nine methodological challenges of the first agenda item-identification of the factors, values or qualities most important to leadership effectiveness. To illustrate these challenges, the authors use their own business leadership research as a case study. This research surveys 127 chairmen, chief executive officers, and presidents-a cross section of successful U.S.A. business leaders, including men and women from all parts of the nation who have diverse industry, racial, ethnic and religious backgrounds. The authors identify where methodological improvements are needed to cope with the challenges of leadership research. They suggest important directions for methodological development and propose three minimum standards for future leadership research.